Analisis Pengaruh Literasi Keuangan, Dukungan Finansial, Lingkungan Sosial, dan Financial Technology terhadap Perilaku Keuangan Mahasiswa (Studi Kasus Mahasiswa FEB Universitas Jambi) - Alberth Cristian Ambarita; Etik Umiyati; Helen Parkhurst (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to (1) identify student characteristics related to financial literacy, financial support, social environment, and financial technology (2) analyze the influence of financial literacy, financial support, social environment, and financial technology on the financial behavior of students at the Faculty of Economics and Business, Jambi University. The research employed a quantitative approach using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the SmartPLS 4 software. A total of 98 respondents were selected through the Slovin formula, consisting of active students from various study programs within the faculty. The results show that financial literacy, financial support, and social environment have a positive and significant effect on students’ financial behavior, while financial technology has a positive but insignificant effect. The R-Square value of 0.757 indicates that 75.7% of the variation in financial behavior can be explained by the four independent variables, while the remaining 24.3% is influenced by other factors not included in the model. These findings suggest that students’ financial behavior is primarily influenced by knowledge and environmental factors rather than technological aspects.